2008
DOI: 10.1902/jop.2008.070421
|View full text |Cite
|
Sign up to set email alerts
|

Ossification of a Collagen Membrane Cross‐Linked by Sugar: A Human Case Series

Abstract: GLYM maintained its barrier effect in five of seven cases for 25 weeks and induced dense new bone along its interface with underlying tissues. To the best of our knowledge, this is the first report on GLYM ossification in humans with direct mineral apposition on glycated collagen and suggests a new concept of tissue-integrated active barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 24 publications
5
38
0
1
Order By: Relevance
“…Additionally, Zubery et al. found evidence of membrane ossification when glycine cross‐linked membranes were used in osseous regeneration surgery . Direct apposition of bone along the side of the barrier and the ossification of the membrane itself may support the hard tissue findings seen in our study.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, Zubery et al. found evidence of membrane ossification when glycine cross‐linked membranes were used in osseous regeneration surgery . Direct apposition of bone along the side of the barrier and the ossification of the membrane itself may support the hard tissue findings seen in our study.…”
Section: Discussionsupporting
confidence: 86%
“…The use of two different membranes introduces an additional variable to be considered; however, the use of each membrane was selected based on the specific properties of the materials used and the lack of intended primary closure over the site. The long‐resorbing OP membrane was placed over the XGS material to contain it during initial healing stages and enabled longer soft tissue exclusion to allow adequate time for osteoprogenitor cells to reach the site and initiate vital bone formation 13,14,23 . It is unknown if the selection of different membranes for the two protocols had an impact on clinical or histologic results; however, the results are similar to other studies in which rapidly resorbing collagen membranes were used to cover the graft material within the socket 17,18,24 …”
Section: Discussionmentioning
confidence: 71%
“…Primary closure over this material is recommended; however, if primary closure is not intended or obtained, a collagen membrane can be placed over the material to stabilize the initial blood clot and contain the bone graft substitute 9,10 . A resorbable collagen membrane composed of tendon‐derived type I porcine collagen cross‐linked by natural ribose glycation (OP) § can be used to occlude gingival cells from downgrowth into extraction sites 12‐14 . Another xenograft protocol that has been suggested for ridge preservation is 90% anorganic bovine bone with 10% porcine collagen fibers (ABBC) ‖ combined with a resorbable bilayer membrane composed of non‐cross‐linked porcine types I and III collagen (BG) ¶ 15…”
Section: Methodsmentioning
confidence: 99%
“…The history of premature membrane exposure may have a negative effect on new bone formation even if soft tissue dehiscence recovers by secondary epithelization. Although ribose-cross linked membranes might be associated with a higher incidence rate of soft tissue dehiscences (Moses et al, 2005;Tal, et al, 2008), the frequency of concomitant inflammatory reactions reported is almost zero (Friedmann et al, 2001 (Zubery, et al, 2007;Zubery et al, 2008).…”
Section: Morphometric Resultsmentioning
confidence: 99%